Calculation of Pile Capacity in Cohesionless Soil by CPT Considering Spatial Variability - MERT, AHMET CAN; YAZICI, GÖKHAN (Çukurova Üniversitesi Mühendislik Fakültesi, 2021)
The study aims to construct a framework for CPT based ultimate pile capacity calculation for cohesionless soils with random field theory. Cone tip resistance (qc) was taken as the spatially varying parameter with a constant mean and changing coefficients of variation. CPT profiles were simulated with random field generations, and the ultimate capacity of a single pile (Qu) was calculated with these simulations. The influence of spatial variation of qc on the variation of Qu was investigated. The proposed framework was finally verified by comparing the results of an actual CPT database and the simulated CPT profiles in the study. The results showed that the critical vertical scale of fluctuation for CPT-based pile capacity calculations was equal to one diameter of pile (dv=1D), and that the method effectively predicted the ultimate pile capacity through simulated CPT profiles with random field. The proposed method is especially recommended for cases where the uncertainty consideration is necessary, yet the site-specific data is limited. The study aims to contribute a simple framework to the methods of CPTbased pile capacity with unceratinty consideration. The propesed method aims to facilitate the pile design framework with limited available data.
Kohezyonsuz Zeminde CPT ile Kazık Kapasitesinin Boşluksal Değişkenlikle Hesabı
Keywords: Cone Penetration Test; Ultimate Pile Capacity; Random Fields; Spatial Variability; Cohesionless Soil